Anda di halaman 1dari 6

# RD Sharma - Mathematics

SHARE
CCE - FORMATIVE ASSESSMENT

Q. 1

Write the value of k for which the system of equations x + y – 4 = 0 and 2x + ky – 3 = 0 has no solution.

Q. 2

2x – y = 5

6x + ky = 15

## has infinitely many solutions.

Q. 3

Write the value of k for which the system of equations 3x – 2y = 0 and kx + 5y = 0 has infinitely many solutions.

Q. 4

Write the values of k for which the system of equations x + ky = 0, 2x – y = 0 has unique solution.

Q. 5

Write the set of values of a and b for which the following system of equations has infinitely many solutions.

2x + 3y = 7

2ax + (a + b) y = 28

Q. 6

For what value of k, the following pair of linear equations has infinitely many solutions?

10x + 5y – (k – 5) = 0
20x + 10y – k = 0

Q. 7

x + 2y– 8 = 0

2x + 4y = 16

Q. 8

x + 3y– 4 = 0

2x + 6y = 7

Q. 1

kx – y = 2

6x – 2y = 3

Q. 2

2x + 3y = 5

4x + ky = 10

## has infinite number of solutions, is

Q. 3

The value of k for which the system of equations x + 2y – 3 = 0 and 5x + ky + 7 = 0 has no solution, is

Q. 4

The value of k for which the system of equations 3x + 5y = 0 and kx + 10y = 0 has a non-zero solution, is

Q. 5

## If the system of equations

2x + 3y = 7

(a + b) x + (2a – b) y = 21

Q. 6

3x + y = 1

## (2k – 1)x + (k – 1)y = 2k + 1

is inconsistent, then k =

Q. 7

ax + by = c

lx + my = n

Q. 8

## If the system of equations

2x + 3y = 7

2ax + (a + b)y = 28

Q. 9

## The value of k for which the system of equations

x + 2y = 5

3x + ky + 15 = 0

has no solution is

Q. 10

## If 2x – 3y = 7 and (a + b) x – (a + b – 3) y = 4a + b represent coincident lines, then a and b satisfy the equation

Q. 11

If a pair of linear equations in two variables is consistent, then the lines represented by two equations are

Q. 12

The area of the triangle formed by the line with the coordinate axes is

Q. 13

Q. 14

Q. 15

Q. 16

## The area of the triangle formed by the lines x = 3, y = 4 and x = y is

Q. 17

The area of the triangle formed by the lines 2x + 3y = 12, x – y – 1 = 0 and x = 0 (as shown in Fig. 3.23) , is